Aspek Budaya Dasar dalam Novel Bumi Cinta Karya Habiburrahman El Sirazy - Erwita, Rini; Hamidin, Hamidin; Chan, Wirsal (Universitas Negeri Padang, 2012)
This research is qualitative with descriptive method. Data for this research is events that existed in Bumi Cinta, the novel, written by Habiburrahman El Shirazy, which have aspects of basic culture. Data source in this research is Bumi Cinta, the novel, written by Habiburrahman El Shirazy. Data collection technique is reading and remarking events from actor’s behavior indication that lead to aspect of basic culture in Bumi Cinta, the novel, written by Habiburrahman El Shirazy. This research generally purposed to describe Bumi Cinta, the novel, written by Habiburrahman El Shirazy, in specific is to analyze descriptively forms of basic culture’s aspect that defined in Bumi Cinta, the novel, written by Habiburrahman El Shirazy. There are eight aspects of basic culture that describe in Bumi Cinta, the novel, by Habiburrahman El Shirazy, that are: (1) human and affection, (2) human and embellishment, (3) human and suffering, (4) human aspect and justice, (5) human and responsibility, (6) human and way of life, (7) human and discomfort, and (8) human and expectation.